Power Relations and Resistance in Naguib Mahfouz’s Layali Alf Laylah: Michel Foucault's Hegemony - Alandira, Palendika; Rohanda, Rohanda; Taufiq, Wildan; Firdaus, Rifqi Muhammad (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This research examines the relationship between power and resistance in Layali Alf Laylah, a novel by Najib Mahfouz, through the lens of Foucault's hegemony theory. This qualitative research employs an analytical descriptive approach. The material object analyzed is the novel Layali Alf Laylah, while the formal object is Foucault's hegemony theory, which explores the influence of power on individuals and the emergence of resistance against established power structures. The analytical descriptive method is utilized to examine the text and to identify the various forms of power and resistance mechanisms embedded within the characters and narrative of the novel. The findings indicate that the novel portrays repressive power dynamics while simultaneously presenting resistance against these power structures through both individual and collective actions. Consequently, the novel not only illustrates the existing power relations but also highlights how resistance plays a crucial role in the process of social change. In conclusion, Layali Alf Laylah offers a nuanced depiction of the interplay between power and resistance within a society shaped by dominant power structures. The novel provides critical insight into the complexities of hegemonic influence and the potential for subversion, reinforcing the dynamic nature of societal power relations. This research contributes to the body of knowledge by providing a deeper understanding of the dynamics of power and resistance in literature, demonstrating how Foucault’s theoretical framework can be applied to analyze social structures within fictional narrative. ملخص يهدف هذا البحث إلى تحليل علاقة السلطة والمقاومة في رواية